Pengaruh konsentrasi pupuk organik cair kulit nanas dan dosis pupuk anorganik terhadap pertumbuhan dan produksi tanaman pakcoy (Brassica rapa L.) - Risda Nurdiani; fedri Ibnusina; Delni Alek Candra (University of Insan Cendekia Mandiri, 2025)
Pakcoy (Brassica rapa L.) is a relatively short-lived agricultural crop that can be harvested in a short time. This study aims to find the concentration of pineapple peel POC nutrition and 50% NPK to replace the role of 100% NPK fertilizer and support the growth and yield of pakcoy plants. The research method used a Randomized Group Design with 4 treatments, namely P1: 100% inorganic fertilizer, P2: 240 mL pineapple peel POC/ 1 L of water + 50% NPK, P3: 260 mL pineapple peel POC/ 1 L of water + 50% NPK, P4: 280 mL pineapple peel POC/ 1 L of water + 50% NPK, six replication. Parameters observed were the number of leaves, leaf width, leaf length, fresh weight, crown weight, root weight, and root length. Based on the results of the study, significant results were obtained in the observation parameter of leaf length (cm), fresh weight (g), root length (cm), while those that were not significant were in the observation parameters of the number of leaves (strands). Leaf width (cm), crown weight (g), root weight (g). From the results of the study, it was found that 260 ml of pineapple peel POC / 1 liter of water + 50% NPK was the best treatment level and could replace the role of 100% NPK. Based on this research, it is recommendded for pakcoy cultivation using nutrition 260 mL pineapple peel POC / 1 L of water + 50% NPK can increase plant growth and production as well as environmentally friendly.